Demoralization of Government Bureaucratic Corruption in East Kutai District Head Ismunandar - Kalalinggi, Rita (Universitas Muhammadiyah Yogyakarta, 2020)
This study uses the literature review method through journals and supporting reports that are related to this study and explained descriptively through data obtained from journals or reports. The findings generated in this study are corruption cases involving regional heads in East Kutai and their ranks are inseparable from the existence of oligarchic politics, all of these cannot be separated from the compatibility of a project. Cases like this are rife in bureaucratic and political elites who sometimes use family connection mechanisms. According to records from the Corruption Eradication Commission (KPK) from 2015 to 2018 in terms of cases and the number of suspects continues to increase. In 2018, the KPK handled 57 cases with 261 suspects and a total loss of Rp385 billion. Where the average cases handled by the KPK per month are five cases with an estimated value of Rp6.6 billion. Corruption acts carried out by the KPK mostly function as chairmen or members of the Regional House of Representatives (DPRD) with a total of 103 suspects. Acts of corruption are often carried out by political elites in the DPR as well as in law enforcement agencies. However, the most vulnerable to corruption is the village. the most vulnerable sector in 2018 is the village budget. There were 96 cases of corruption related to the village budget involving 133 suspects with state losses of Rp. 37.2 billion. Meanwhile, the sector that caused the highest state loss was the banking sector amounting to Rp2,100 billion (16 cases).Â